2019
DOI: 10.1088/1361-665x/aadb6c
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical modeling and experimental verification of a direct write nanocomposite

Abstract: Piezoelectric materials are currently among the most promising building blocks for sensing, actuation and energy harvesting systems. However, these materials are limited in certain applications due to their lack of machinability as well as their inability to conform to curved surfaces. One method to mitigate this issue is through additive manufacturing (direct printing) of piezoelectric nanocomposites, where piezoelectric nanomaterials are embedded in a polymer matrix. Although significant progress has been ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Due to the crystallographic structure of piezoelectric crystals, the magnitude of the electrical response is dependent on the direction of applied stress 197. Nafari and Sodano used DIW to produce a piezoelectric composite made of shear‐aligned barium titanate nanowires suspended in polydimethylsiloxane (PDMS) 198. An electromechanical model and experimental verification demonstrated that aligning the nanowires longitudinally with the applied stress can increase the electromechanical coupling up to 90% that of pure lead zirconate titanate (PZT‐7A) 199.…”
Section: Fluid Shear Patterningmentioning
confidence: 99%
“…Due to the crystallographic structure of piezoelectric crystals, the magnitude of the electrical response is dependent on the direction of applied stress 197. Nafari and Sodano used DIW to produce a piezoelectric composite made of shear‐aligned barium titanate nanowires suspended in polydimethylsiloxane (PDMS) 198. An electromechanical model and experimental verification demonstrated that aligning the nanowires longitudinally with the applied stress can increase the electromechanical coupling up to 90% that of pure lead zirconate titanate (PZT‐7A) 199.…”
Section: Fluid Shear Patterningmentioning
confidence: 99%
“…In addition to the difficulties of poling, mechanical stress transfer between the soft matrix and the stiff inorganic inclusions is another critical issue. Using high-aspect-ratio piezoelectric fillers and aligning them improves the mechanical coupling of the composite and results in higher piezoelectric response. Andrew et al improved by more than 200% the d 33 of 20%vol PZT/PVDF composite films by using nanowires instead of quasi-spherical particles. This effect can be understood by considering the more efficient stress transfer in nanocomposites with high aspect ratio anisotropic nanoparticles .…”
Section: Piezoelectric Composite Fibersmentioning
confidence: 99%
“…183 Alignment of anisotropic particles is also important to ensure an efficient stress transfer, and a greater piezoelectric response with the polar axis of the nanoparticles along the axis of piezoelectric activity. Nafari and Sodano 179 demonstrated that a composite made of 40 wt % BaTiO 3 aligned nanowires with an aspect ratio of 10 in PDMS film has its d 33 coefficient enhanced by 100% compare with randomly oriented nanowires.…”
Section: Piezoelectric Composite Fibersmentioning
confidence: 99%
“…The more non-zero elements the vector Y contains, the stronger is synchronization among the cells at that frequency which is determined by the strength of κ ij /s i . For simple demonstration of the concept and capability of our proposed approach, we have generated 2000 nonintersecting nanofibrils using a packing algorithm [77]. The nanofibrils are generated such that they are all confined within a box with dimensions 8 × 8 × 4 µm 3 (∼0.3% volume fraction) to represent a biofilm sample.…”
Section: Appendix Amentioning
confidence: 99%